Evaluation of Estrone Liposomes using Microfluidics for Breast Cancer Therapy - Al Bostami, Rouba D. (2023)
A Master of Science thesis in Biomedical Engineering by Rouba Darwish Al Bostami entitled, “Evaluation of Estrone Liposomes using Microfluidics for Breast Cancer Therapy”, submitted in November 2023. Thesis advisor is Dr. Mohamed Abdelgawad and thesis co-advisor Dr. Ghaleb Al Husseini. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).